Investigation and genetic confirmation of the Cryptosporidium species in fish handlers in Baghdad city. - Obead , Noor Majed; Alhaboubi, Amer Rasool (Journal of Advanced Veterinary and Animal Research, 2025)
Objective: The present study aims to investigate molecular confirmation for Cryptosporidium species in fish handlers in Baghdad City, central Iraq. Materials and Methods: Sixty stool samples were collected between early November 2023 and late April 2024. All samples were examined phenotypically using a modified Ziehl-Neelsen stain and genotypically (nested polymerase chain reaction technique) based on a partial sequence of 18S rRNA genes with sequencing and phylogenetic tree analysis. Results: The total molecular results identified Cryptosporidium parvum with an infection rate of 45% (27/60). A higher infection rate of 51.9% (14/27) was found in the age group between 15 and 35 years, and male handlers recorded a lower infection rate (45%) than females (41.6%). April had a higher elevation in the infection rate of 60% (6/10) than other months. Conclusion: The C. parvum was the only species found in fish handlers, and these local isolates have higher similarity with other isolates of China and Iran. J. Adv. Vet. Anim. Res., 12(1): 1–7, March 2025 http://doi.org/10.5455/javar.2025.l866